PENGARUH PENAMBAHAN ABU SEKAM PADI TERHADAP KUAT TEKAN BETON K-225 - Arifal Hidayat (Jurnal APTEK, 2011)
The paddy chaff is a waste of paddy hulling, and it contains dominant silica which is as big as 93 % and almost has the same contain of silica that exist on micro-silica of factory brand. With its character, if it mixed into concrete mixture, it will fix the characteristic of concrete. In this research, the ash of paddy chaff is added into the mix of normal concrete, C- 225 Kg / Cm2, with the variation of the ashes chaff 0%, 2,5%, 5%, 7,5%, and 10%, heavy of percentage of the ashes, it was taken based of the weight of cement. The effect of this research is to know the pressing strong point of concrete, is reached from the chaff ash mixture paddy in concrete k 225 kg / cm.The design of concretes used the standard of SK.SNI.T-15-1990-03 that default in Indonesia. The object of the test, that is made for each one ash of percentage increase chaff is as much 3 samples, with cylinders printed of diameter is about 15 cm and tall is about 30 cm.